Approaches to Corporate Debt Restructuring in the Wake of Financial Crises - Laryea, Thomas (Washington, D.C. : International Monetary Fund, 2010)
This paper starts from a discussion of the economic case for moderated government intervention in debt restructuring in the nonfinancial corporate sector. It then draws on lessons from past crises to explain three broad approaches that have been applied to corporate debt restructurings in the aftermath of a crisis. From there, it addresses challenges in designing and implementing a comprehensive debt restructuring strategy and draws together some key principles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet